Linguistic Activities for Improve Listening and Speaking Skills/ الأنشطة اللغوية لتنمية مهارة الاستماع والكلام - Chamidah, Dewi; Istiqomah, Rosyida (Ijaz Arabi Journal of Arabic Learning, 2021)
Listening and speaking skills are important in learning languages, especially Arabic. A language activity needs to be held to support the student's skills. Linguistic activities are all kinds of activities that are implemented to learn a language. The purpose of this research is to uncover and analyze the appropriate activities and the supporting and inhibiting factors of these activities at "Alfarisi" Arabic course, Pare, Kediri. This research is qualitative research using the case study method. Data collection techniques use observation, interviews, and documentation. The results of this research indicate that: Linguistic activities to improve listening skills in "Alfarisi" Arabic Course include: listening to story, listening to music, listening to conversations. Linguistic activities to improve listening skills include: speech, conversations, storytelling, memorize the tashrif, memorize the conversations, drama, memorize the Qur’an of juz amma which means 30 juz, and memorize the supplications in prayer. The external motivation in developing listening and speaking skills are given motivation, reward, and correction of student speech wherever they are. The obstacles faced are the lack of memorizing vocabulary, students feel embarrassed, students do not understand the material, the lack of supervisors who are present in this course, and cultural differences in the student community.